Kolase Kapas: Skill Membangun Kemampuan Seni Bagi Anak Usia Dini - Binsa, Ucik Hidayah; Solikhatin, Muthik; Irbah, Ariq Nurjannah (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2022)
Abstract: Art ability is one of the main aspects that must be developed in improving children's skills. Art also has a very important influence in stimulating the development of a child's brain. The purpose of this study was to find out how the artistic abilities of group A1 students and how to improve the artistic abilities of group A1 students through cotton collage at RA Muslimat NU XIII Nawa Kartika Talok. This research includes Classroom Action Research. The subjects of this research were group A1 students of RA Muslimat NU XIII Nawa Kartika Talok, which consisted of 17 students. This research was conducted in two cycles, with several stages, namely action planning, action implementation, observation and reflection. The results showed that there was a significant increase with the completeness of the class target of at least 82.35% in cycle 2. Thus overall the artistic abilities of the children were in a very good stage of development (BSB) and through this cotton collage activity was able to improve artistic abilities in group students A1 RA Muslimat NU XIII Nawa Kartika Talok.